Cohesively Enhanced Conductivity and Adhesion of Flexible Silver Nanowire Networks by Biocompatible Polymer Sol–Gel Transition. (29th January 2015) - Jin, Yunxia; Li, Lu; Cheng, Yuanrong; Kong, Lingqiang; Pei, Qibing; Xiao, Fei
Abstract : Silver nanowire (AgNW) networks are a promising candidate to replace indium tin oxide (ITO) as transparent conductors. In this paper, a novel transparent composite conductor composed of AgNW/biocompatible alginate gel on a flexible polyethylene terephthalate (PET) substrate, with synchronously enhanced adhesion and reduced resistivity, is prepared without high‐temperature annealing. The sheet resistance of the flexible AgNW/PET film reduces from 300 to 50.3 Ohm sq −1 at transmittance of 94%. The optical and electrical performance is superior to that obtained from the flexible ITO film on PET. Meanwhile, the sheet resistance does not show great change after tape test, suggesting a good adhesion of AgNW to the polymer substrate. Moreover, the AgNW composite film shows a good stability to resist long‐term storage, solvent damage, and ultrasonication. Finally, polymer solar cells employing the composite AgNW film as the electrode are realized, displaying an efficiency of 2.44%. Abstract : Flexible Ag nanowire (NW)/Ca alginate composite transparent electrodes with cohesively improved adhesion and conductivity are prepared without high‐temperature annealing. The bivalent calcium ions cross‐link the alginate under the AgNW networks to form water‐resist alginate gel to bond the AgNWs tightly on the substrate; the chloride ions detach the stabilizer on the surface of the Ag nanowire to trigger the sintering.